Market orientation vs. inovativeness of SMEs of Podlaskie province - Ejdys, Joanna (Business: Theory and Practice, 2015)
This research aims to examine the impact of marketing orientation on the innovation level among Small and Medium Size (SMEs) from Podlaskie Province. A survey utilizing a questionnaire was conducted among 137 companies in the Podlaskie Voivodeship. Altogether 3 hypotheses concerning marketing orientation and innovativeness level have been examined with the use of the hierarchical regression techniques. The relation between three types of marketing orientation and innovativeness has been analysed: customer orientation, competitor orientation and interfunctional coordination. The research results show that marketing orientation has a positive total effect on improving innovativeness. The conclusions suggest, contrary to the marketing orientation sources, that customer orientation hinder marketing innovation. A positive interrelation between customer orientation and competitor orientation, as a component of marketing orientation and innovation was supported. The positive interrelationships between inter-functional orientation and innovativeness was rejected. The study explores the relationship between marketing orientation and innovativeness, thus theoretically contributing to marketing orientation literature. Moreover, relevant ramifications are provided for management, concerning the ways to boost the level of innovativeness.